A quantum chemical DFT/HF study on acidity constants of some benzothiazole and thiazole derivatives - Tay, Funda; Duran, Murat; Demirayak, Şeref (Council of Scientific and Industrial Research, 2014)
The acid dissociation (K-a) constants of some 4-and/or 6-substituted-2-aminobenzothiazole compounds have been investigated theoretically. The gas and aqueous phase geometries, thermal and solvation free energies have been calculated with full geometry optimization by using HF (6-31G(d)) and B3LYP (6-31G(d)) methods for 2-aminobenzothiazole, 2-aminothiazole derivatives and their fixed models. From the calculated acidity constants of investigated compounds, it has been detected that the protonation occurs at the the nitrogen atom of the amino group for 2-aminobenzothiazoles and at ring nitrogen atom for 2-aminothiazoles. Acceptable correlations have been observed between theoretically (HF and B3LYP) and experimental pK(a) values of the molecules with regression coefficients (R-2 = 0.98, 0.86) and (R-2 = 0.98, 0.85) for the protonation of benzothiazole and thiazole molecules, respectively. Theoretical calculations also show that basicity of the studied compounds increase in the presence of electron donor substituents.
WOS: 000330160400004
Keywords: 2-Aminobenzothiazole; 2-Aminothiazole; pK(a) Calculation; Theoretical Calculations; PCM